2009
DOI: 10.1111/j.1751-553x.2008.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of homozygous sickle cell disease: 102 patients over 60 years

Abstract: Summary Earlier reports on homozygous sickle cell (SS) disease have been biased by severely affected cases. The Jamaican clinic which seeks to avoid such bias has 102 patients surviving beyond 60 years. The objective of this study was to examine the features of elderly cases and assess factors determining survival and the behaviour of this disease with advancing age. A retrospective review of all cases and prospective assessment in survivors was conducted at The Sickle Cell Clinic at the University of the West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…In a previous report from Jamaica, survival to age 60 years was associated with female gender and higher fetal haemoglobin (HbF). Elderly survivors present some features of intrinsic mildness but also manifest age-related amelioration of painful crises and falling haemoglobin levels from progressive renal damage (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report from Jamaica, survival to age 60 years was associated with female gender and higher fetal haemoglobin (HbF). Elderly survivors present some features of intrinsic mildness but also manifest age-related amelioration of painful crises and falling haemoglobin levels from progressive renal damage (10).…”
Section: Discussionmentioning
confidence: 99%
“…This study was remarkable because the prevailing thought at the time was that survival beyond 30 years was rare. The second case series identified 102 patients who survived beyond 60 years (10). This longevity was achieved without the use of disease-modifying therapies such as chronic transfusion and hydroxyurea, and pre-dated much of the recent public health initiatives that affect survival, emphasizing the role of biological factors as disease modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…5,11,15 Surprisingly, studies in Saudi Arabia and Jamaica found a significantly higher rate of preeclampsia and eclampsia in pregnancies complicated by SCD, even though better pregnancy outcome was observed compared with the studies conducted in Africa. 16,17 The higher mortality rate among women with SCD in countries like Ghana may be caused by inadequate healthcare support particularly for pregnant women. 18 In Ghana about 2% of neonates are affected by SCD leading to 14,000 new cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…3 In keeping with this trend, in 2008, advanced CKD was reported as present in 24% of SCD patients who had survived to 60 years of age or more and was the cause of death in 45% in those who died above this age. 4 Renal dysfunction is relatively more common and more severe in patients with HbSS and HbSb 0 genotypes than in patients with HbSC or HbSb 1 thalassemia. 3,5 In our patient cohort, both the incidence and degree of microalbuminuria are much lower in adults with HbSC disease when compared with HbSS or HbSb 0 .…”
Section: Natural History Epidemiology and Genetic Modifiersmentioning
confidence: 99%